Urban geometry and electrical energy consumption in a tropical city - Souza, Léa C.L. [UNESP]; Pedrotti, Flávia S.; Leme, Francesco T. (My University, 2004)
A study to estimate a correlation between urban geometry and electrical energy consumption of Bauru, a tropical city situated in Brazil, is presented. The study suggests a direct correlation of electrical energy consumption to the urban geometry canyon, and also establishes relationship between sky view factor and the temperature and energy consumption. A comparative study of energy consumption during summer and winter seasons, was also presented. The relationship between temperature and energy consumption to the urban geometry of the canyon could be used by architects to optimize the energy use of a city.